On the stability of oligo(ethylene glycol) (C11EG6OMe) SAMs on gold: behavior at elevated temperature in contact with water. - Zorn, S; Skoda, M; Gerlach, A; Jacobs, R; Schreiber, F (2011)
In this study the temperature dependent confor-mation of hexa(ethylene glycol) self-assembling monolayers (SAMs) under aqueous conditions (in situ) is investigated. To this end characteristic absorption modes in the fingerprint region (1050-1500 cm(-1)) were monitored with real-time polarization modulation infrared spectroscopy. We found a temperature induced conformational change from predominantly helical to helical/all-trans. The process may be divided into two temperature regimes. Up to 40 °C the process is reversible after drying the monolayers in air and successive reimmersion in water, indicating a strong binding of the water molecules to the SAM. At higher temperatures, the conformational change is irreversible. Additionally, a rapid change to a larger mode width and a shift of the mode position to higher wavenumbers (blue-shift) at about 50 °C indicates structural changes caused by decreasing crystallinity of the SAM. While the conformational changes up to 40 °C are supposed to originate from an increased conformational freedom in combination with a stronger interaction with water molecules, the irreversibility and rapid change of mode characteristics at higher temperatures indicate chemical degradation. Complementary measurements in air show a fast and virtually complete reversibility up to 40 °C underlining the effect of the interaction of the ethylene glycol moiety with water. At temperatures above 50 °C modes indicating ester and formate groups appear, supporting the idea of chemical degeneration. Moreover, the temperature behavior is coverage dependent. At incomplete coverage the structural order of the SAM starts decreasing at lower temperatures. This study shows, that the conformational and structural change of hexa(ethylene glycol) SAMs at elevated temperature is an interplay of conformational changes of the SAM, its interaction with water and at higher temperatures its chemical degradation. Our experiments also underline the importance of the in situ analysis on the film structure.